Inhibition of MRP1/ABCC1, MRP2/ABCC2, and MRP3/ABCC3 by Nucleoside, Nucleotide, and Non-Nucleoside Reverse Transcriptase Inhibitors - Weiß, Johanna; Theile, Dirk; Ketabi-Kiyanvash, Nahal; Lindenmaier, Heike; Haefeli, Walter E. (Drug metabolism and disposition, 2007)
Many drug interactions with drugs used for the therapy of human immunodeficiency virus (HIV) occur at the level of different cytochrome P450 isozymes. Increasing evidence suggests that antiretrovirals may also modify activity and expression of active drug transport systems. Such interactions may alter drug absorption, elimination, and also drug distribution and reach clinical importance if thereby access to the target site is affected. Beyond P-glycoprotein, the family of multidrug resistance-related proteins (MRP/ABCC) substantially contributes to the elimination of numerous drugs and their metabolites. Because the interaction of MRPs with non-HIV protease inhibitor antiretrovirals has not been studied thoroughly, we investigated whether important non-nucleoside reverse transcriptase inhibitors (NNRTI) (delavirdine, efavirenz, and nevirapine), nucleoside reverse transcriptase inhibitors (NRTI) (abacavir, emtricitabine, and lamivudine), and tenofovir as a nonnucleotide reverse transcriptase inhibitor can interact with MRP1, MRP2, and MRP3 in vitro. Inhibition of these ABC transporters was quantified by confocal laser-scanning microscopy using the 5-chloromethylfluorescein diacetate assay. With the exception of abacavir, which had no effect on MRP3, all the test compounds increased intracellular 5-chloromethylfluorescein fluorescence in a concentration-dependent manner, and this effect was observed in all the overexpressing cell lines but not in the parental cell line, indicating inhibition of MRP1, MRP2, and MRP3. In conclusion, the present study provides the first evidence for a significant and concentration-dependent inhibition of MRPs by NNRTI, NRTI, and tenofovir, which was most pronounced for delavirdine, efavirenz, and emtricitabine, suggesting that this might contribute to some of the known drug interactions impairing HIV therapy and also to the superior effectiveness of combination pharmacotherapy.
Gesehen am 12.05.2021